Interstitial Lung Disease in Women of Child-Bearing Age - Mylvaganam, Ruben; Dua, Sakshi; Nelson-Piercy, Catherine; Mathur, Aditi (Seminars in Respiratory and Critical Care Medicine, 2017)
Interstitial lung disease (ILD) is an inflammatory and fibrotic infiltrative process of the lung that is often associated with collagen vascular disease in women. Untreated, it results in collagen deposition in the lung interstitium that can lead to a slow suffocating death. Pregnancy planning is often not discussed with women who have ILD due to concerns about potentially aggravating the disease process, or due to lack of knowledge about the safety of medications used to treat ILD. With improved understanding of the pathophysiology of both autoimmune disease and ILD, it has become clear that safe, planned pregnancies are possible in most women with ILD. In this article, our aim is to review diagnosis, treatment, and disease course of ILD in women who are planning a pregnancy or are pregnant. Better understanding of the disease process and knowledge of safe treatments will likely lead to improved pregnancy planning in women with ILD.
Keywords: interstitial lung disease; pregnancy; connective tissue disease; collagen vascular disease; teratogenic